ФІЛ ОСОФІЯ ОСВІТ И ЯК НАВЧАЛЬНА ДИСЦИПЛІ НА: УКРАЇНСЬКІ РЕ АЛІЇ - Radchenko, N (Continuing Professional Education: Theory and Practice, 2019)
The article examines the current state of philosophy of education in Ukraine and problems of philosophy of education as an academic discipline. In particular, the question of the purpose of the course “Philosophy of Education” in connection with the state of humanitarian education in Ukraine, considers approaches to the content of the course “Philosophy of Education” and the problem of methodological support for the course.